Academic Writing Needs of International Psychology PhDs in a South African University - Samuel UMOH; Matshepo Catherine MATOANE (Studia Universitatis Babes-Bolyai, 2023)
The paper examines the academic writing experience amongst international psychology PhD students at a South African public university. The paper also discusses the challenges of academic writing and the support structures of academic writing. Sixteen (16) international students studying at PhD level in psychology were selected by purposive sampling from a public South African university in KwaZulu-Natal. Drawing from generated by iproposalss, findings suggest that participants experienced academic writing challenges in drafting PhD proposal, supervisor's feedback and plagiarism. Academic writing challenges were aggravated for international PhD students from non-native English-speaking countries. Findings also suggest that university support structures such as academic writing retreats improved the academic writing of participants and exposed them to the rigors of academic writing.